2007
DOI: 10.1017/s002202990700283x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary feeding at milking and minimum milking interval effects on cow traffic and milking performance in a pasture-based automatic milking system

Abstract: In extensive pastoral dairy farming systems herds graze 12 months of the year with the majority fed a near-100% pasture or conserved pasture diet. The viability of automatic milking in these systems will depend partly upon the amount of supplementary feed necessary to encourage cows to walk from the pasture to the milking unit but also on the efficient use of the automatic milking system (AMS). This paper describes a study to determine the importance of offering concentrate in the milking unit and the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
3
23
0
1
Order By: Relevance
“…Milking frequencies (2.37 ± 0.02/day in HC and 2.35 ± 0.02/day in LC) observed in our study were comparable with those reported by Spörndly and Wredle (2005). Other studies performed in fully grazing systems by Jago et al (2007) and Lyons et al (2013b) in New Zealand and Australia, respectively, recorded less milkings/day: 1.7 milkings/cow per day (Jago et al, 2007) and 1.5 milkings/cow per day (Lyons et al, 2013b). Milking permission time does not seem to be a limiting factor as cows were allowed to be milked after a 4-h interval, similar to Lyons et al (2013b), while in Spörndly and Wreddle (2005), the time elapsed between two milkings must have been greater than 6 h. In the present study, high concentrate level increased the robot visitations but also caused more RM in HC.…”
Section: Impact On Voluntary Cow Trafficsupporting
confidence: 88%
See 2 more Smart Citations
“…Milking frequencies (2.37 ± 0.02/day in HC and 2.35 ± 0.02/day in LC) observed in our study were comparable with those reported by Spörndly and Wredle (2005). Other studies performed in fully grazing systems by Jago et al (2007) and Lyons et al (2013b) in New Zealand and Australia, respectively, recorded less milkings/day: 1.7 milkings/cow per day (Jago et al, 2007) and 1.5 milkings/cow per day (Lyons et al, 2013b). Milking permission time does not seem to be a limiting factor as cows were allowed to be milked after a 4-h interval, similar to Lyons et al (2013b), while in Spörndly and Wreddle (2005), the time elapsed between two milkings must have been greater than 6 h. In the present study, high concentrate level increased the robot visitations but also caused more RM in HC.…”
Section: Impact On Voluntary Cow Trafficsupporting
confidence: 88%
“…Effect of minimum milking interval was studied in a pasturebased AMS by Jago et al (2007). They concluded that larger MI than 12 h could be targeted without negative impact on MY.…”
Section: Impact On Voluntary Cow Trafficmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only few published studies have explored the realized benefits of AMS in pasture-based farms (Jago et al, 2007;Lyons et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the milk response to changes in milking frequency could be highly variable both within and between cows and feeding systems (Utsumi, 2011;Lyons et al, 2014). In previous studies, the location and amount of partial mixed ration (PMR) (Sporndly and Wredle, 2004), the timing of PMR feeding (Lyons et al, 2013b) or the level of concentrate offered in the AMS (Jago et al, 2007) had little or no effects on the number of milkings/day and milk production. Conversely, the walking distance to pasture and both the size and frequency of pasture breaks/day can change the grazing behavior of cows and the subsequent distribution of milkings at the AMS ( Ketelaar-de Lauwere et al, 2000;Lyons et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%